Mongol invasion and the destruction of Wrocław in April of 1241. Problem of interpretation of archaeological sources - Piekalski, Jerzy (Archaeologia Historica Polona, 2025)
This article aims to verify the current knowledge on the course of the Mongol raid on Wrocław in the spring of 1241. An attempt has been made to confront the historical tradition presented by the 15th-century chronicle by Jan Długosz with the results of archaeological research. The scope of destruction and reconstruction of wooden buildings in the 13th century was analysed based on a long series of dendrochronological dates. That research confirmed that most houses were indeed burnt down around 1241. However, no traces of resistance and city defence have been confirmed. Therefore, the chronicler’s information about the inhabitants of Wrocław burning the settlement themselves and finding shelter on the Cathedral Island should be considered trustworthy.